Children and Adults in Second-Language Learning - Hadna Suryantari (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2018)
Learning is a process in which people study to acquire or obtain knowledge or skill. Second language learning is a process of internalizing and making sense of a second language after one has an established first language. Learning a second language is different from learning first language. Second language is learnt after one is able to speak and has absorbed knowledge, which influences himÂ in learning a second language. Most of us believe that children are better than adults in learning second language. This statement is supported by common observation stated that young second-language learners seems to be able to learn another language quickly by exposure without teaching. In this article, the writer tries to present how children and adults in second-language learning based on factors involved in it. Steinberg (2001) states that there are three factors involved in second-language learning. The first is psychological category. It includes intellectual processing which consists of explication and induction process, memory, and motor skills. Then, social situation consists of natural situation and classroom situation. The last is other psychological variables. It consists of ESL or EFL community context, motivation, and attitude. It is complex to determine whether children or adults are better in second-language learning. The common belief that children are better than adults has been proved, although with some qualification regarding the classroom situation. Put another way, adults do not do best in any situation. In the natural situation of language learning, it is determined that young children will do better than adults, and so will older children. It is not even uncommon for young children to learn a second language in a year or less. Therefore, children do better than adults. In the classroom situation, older children will do better than adults. However, young adults will do better than young children to the extent that the young childrenâ€™s classroom is not a simulation of the natural situation. In the simulation case, young children will do better.